Assessing Inequality in Health Service Accessibility Based on Hospital Distribution in Indonesia - Mahqfiroh, Juliatul; Kosasih (Journal of Health Policy and Management, 2025)
Background: The distribution of health facilities is an essential indicator to improve public health services in Indonesia. However, the country’s archipelagic geography and uneven population density create challenges in ensuring equal access. This study aimed to analyze hospital distribution in Indonesia based on provinces and main islands to evaluate inequality in health service accessibility. Subjects and Method: A comparative descriptive study was conducted using secondary data. Hospital data were obtained from the Hospital Information System (SIRS) of the Ministry of Health (2024), and population data were retrieved from the Central Statistics Agency (BPS) report (2023). A total of 3,209 hospitals were identified across 38 provinces and grouped into seven island clusters: Java, Sumatra, Sulawesi, Kalimantan, Papua, Maluku, and Bali–Nusa Tenggara. The population-to-hospital ratio was calculated, and hospital distribution was further analyzed by province, island, and hospital class. Results: Java accounted for the largest number of hospitals (1,622) due to its high population and better infrastructure. In contrast, Eastern regions such as Papua (73) and Maluku (53) showed limited availability. Inequalities were also found in hospital classes, where advanced hospitals (Class A and B) were concentrated in Java, while peripheral regions were dominated by Class C and D facilities. This disparity forces residents in remote areas to travel long distances for adequate care. Conclusion: Unequal hospital distribution highlights the urgent need for equitable health infrastructure development and strategic resource allocation policies to ensure fair access to health services across Indonesia.